Bioaccumulation of some Heavy Metals in Red mullet (Mullus barbatus) and Common pandora (Pagellus erythrinus) in Zliten Coast, Libya - Keri Alhadi Ighwela; Ragab Farag Al-Kazaghly; Mohamed Hamid (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight Investigated in heavy metal bio-accumulation in red mullet (Mullus barbatus) and Common pandora (Pagellus erythrinus) collected in Zliten Coast, Libya.Based on the samples collected, the muscle tissue of fish species may be considered suitable for human consumption.The metal concentration levels observed were in range of acceptable limits proposed by regulations of WHO and FAO.AbstractThe current study aimed to determine the heavy metal concentration like as copper (Cu), zinc (Zn), lead (Pb), cadmium (Cd) and mercury (Hg) in the liver, gills, gonad and muscles in two fish species (red mullet (Mullus barbatus), and common Pandora (Pagellus erythrinus) collected from the Zliten coast in Libya. The levels of heavy metals were determined by using an atomic absorption spectrophotometer (AAS). The results showed that the concentration of heavy metals in the sampled fishes less than the permissible limits for human consumption. In addition, the bioaccumulation for Cu, Pb, Cd, and Hg by both fish species was: liver >gills > gonads > muscles, while Zn follows the sequence: gonads > liver > gills > muscles.